2022
DOI: 10.1002/ehf2.13933
|View full text |Cite
|
Sign up to set email alerts
|

Association of lipoprotein (a) and 1 year prognosis in patients with heart failure with reduced ejection fraction

Abstract: AimCurrent study was to evaluate relationship between baseline serum lipoprotein (a) [Lp(a)] level and prognosis in patients with heart failure with reduced ejection fraction (HFrEF) and to explore whether the relationship would be modified by baseline high-sensitivity C-reactive protein (Hs-CRP) level. Methods and resultsThis is an observational prospective study. HFrEF patients from outpatient clinic were consecutively recruited (n = 362). Based on Lp(a) cutoff (30 mg/dL), patients were divided into normal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Based on information from Refs. [ [1] , [2] , [3] , [4] , [5] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [32] , [33] , [34] , [35] , [36] , [37] , [44] , [45] , [46] , [47] , [48] , [49] , [50] ]. The elements of the figure were created using SERVIER MEDICAL ART (CC BY 4.0).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on information from Refs. [ [1] , [2] , [3] , [4] , [5] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [32] , [33] , [34] , [35] , [36] , [37] , [44] , [45] , [46] , [47] , [48] , [49] , [50] ]. The elements of the figure were created using SERVIER MEDICAL ART (CC BY 4.0).…”
Section: Discussionmentioning
confidence: 99%
“…Increased Lp(a) levels are associated with a higher risk of HF, especially HFpEF, by 109–153 % [ 32 ]. Elevated Lp(a) level is associated with higher risk of CV mortality in HFrEF patients (HR = 1.22; 95 % CI: 1.04–1.64) [ 33 ].…”
Section: Lipoprotein (A)mentioning
confidence: 99%
“…Some studies report an increased risk of IHD and MI with high Lp(a) levels in individuals with CRP ≥ 2mg/L, although findings are not consistently significant (33)(34)(35)(36). Large cohort studies have provided mixed results on the association between Lp(a), Hs-CRP, with cardiovascular risk, suggesting variability by race, sex, and specific cardiovascular outcomes (37)(38)(39)(40)(41). Notably, in certain populations, elevated Lp(a) levels combined with high Hs-CRP significantly correlate with increased risks of major adverse cardiovascular events (MACE), heart failure rehospitalization, and cardiovascular death, while in other populations, such associations have not been observed (38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Large cohort studies have provided mixed results on the association between Lp(a), Hs-CRP, with cardiovascular risk, suggesting variability by race, sex, and specific cardiovascular outcomes (37)(38)(39)(40)(41). Notably, in certain populations, elevated Lp(a) levels combined with high Hs-CRP significantly correlate with increased risks of major adverse cardiovascular events (MACE), heart failure rehospitalization, and cardiovascular death, while in other populations, such associations have not been observed (38)(39)(40)(41). Furthermore, adding other biomarkers like residual cholesterol or D-dimer to the Lp(a) and Hs-CRP combination has shown that the highest levels of these markers correlate with the greatest risk of adverse outcomes in CHD patients (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, elevated Lp(a) (≥30 mg/dL) is associated with higher serum N-terminal pro-B natriuretic peptide levels and lower left ventricular ejection fraction at follow-up (54). Increased cardiovascular mortality and hospitalization rates are reported within the first year of the diagnosis of heart failure in those with high Lp(a) (≥30 mg/dL) (55).…”
Section: Clinical Implications Of High Lp(a)mentioning
confidence: 97%